Betye Saar: Still Tickin’ - Jennifer McCabe (Panorama, 2016)

(untitled)
Scottsdale in the spring is a chaotic convergence of spring training and outdoor art festivals. At the cultural epicenter is the Scottsdale Museum of Contemporary Art, which recently featured a late-career retrospective of the distinguished artist Betye Saar (b. 1926).